A CRIMINAL INVESTIGATION OF THE CRIMINAL STEALING THAT CAUSES THE DEATH OF PERSONS CONDUCTED BY CHILDREN - Hanung Hendratmoko; Ira Alia Maerani (Law Development Journal, 2020)
The crime of theft with violence is regulated in Article 365 of the Criminal Code. Ironically, this crime is committed by someone who is considered a child in the eyes of the law. This writing discusses the mechanism of investigation, constraints and solutions in the implementation of the mechanism for investigating the crime of theft with violence that causes the death of a person committed by a child.The approach method used in this research is the sociological juridical approach. The specification of this research is descriptive analysis and the source of the data that I use comes from primary data and secondary data. This writing uses an analytical knife based on the theory of justice and the theory of punishment.The mechanism for investigating the crime of theft with violence that causes the death of people is carried out starting from the existence of police reports, investigations, investigations, arrests and detention, searches, seizures, witness statements, and statements of suspects. Obstacles in implementing the investigation mechanism are internal and external constraints. The solution to the obstacle is: the investigator confirms to the suspect's legal adviser to always be present and accompany the suspect in the investigation process, the investigator maximizes his performance to look for evidence according to the maximum time limit, the investigator tries to take an emotional approach, the investigator is assisted by the Correctional Center (BAPAS) provide understanding to children to stay calm.